First isolation of viable Toxoplasma gondii from a black mangabey (Lophocebus aterrimus) reveals the emergence of the Africa 1 lineage in East Asia. - Yiheng Ma; Liulu Yang; Yurong Yang (PLoS Neglected Tropical Diseases)
Toxoplasma gondii is an intracellular protozoan whose intermediate hosts encompass nearly all warm-blooded animals, including humans and non-human primates (NHPs). In this study, molecular, serological, immunohistochemical and bioassay methods were used to investigate T. gondii infection in 17 captived NHPs in zoos from China between 2022 and 2023. The infection rate was higher in New World NHPs (83.3%) than in Old World NHPs (16.7%) (P = 0.2424). A viable strain of T. gondii was successfully isolated from the tissues of a black mangabey (Lophocebus aterrimus). The strain designated as TgMonkeyCHn3 was genotyped as ToxoDB #6, which had demonstrated virulence in Swiss Webster outbred mice. The ROP18/ROP5 allele combination was identified as 1/3. The emergence of this strain highlights the increased genetic diversity of T. gondii in East Asia and presents new challenges for the prevention of toxoplasmosis, particularly in captive NHPs. To the best of our knowledge, this is the first report of the ToxoDB genotype #6 isolated in East Asia and the black mangabey is a new host for T. gondii.